Male university peer-educator students remaking masculinities in the context of gender-based violence - Ngubane, S.; Singh, S. (South African Journal of Higher Education, 2026)
Widespread violence perpetrated by men against women has put masculinities under the spotlight. This article draws on the data from a broader qualitative study with male university peer-educator students (MUPES) in South Africa[1]. It focuses on MUPES’ perspectives on the connections between masculinities and gender-based violence (GBV) and how they envision masculine transformation towards preventing GBV at universities. We worked with a purposefully selected group of MUPES and drew on theories of masculinities to thematically analyse the data from individual interviews and focus group discussions. The findings show that men are not always active producers of violence. While some intermittently reproduced hegemonic versions of masculinity that legitimate violence, most scrutinised and challenged the socio-cultural norms that valorise it. Not only did MUPES actively deconstruct some hegemonic masculine norms, but they also proposed a remaking of them and encouraged positive change in other men. We argue that male peer educators are valuable resources that may be engaged in university GBV intervention. Widespread violence perpetrated by men against women has put masculinities under the spotlight. This article draws on the data from a broader qualitative study with male university peer-educator students (MUPES) in South Africa[1]. It focuses on MUPES’ perspectives on the connections between masculinities and gender-based violence (GBV) and how they envision masculine transformation towards preventing GBV at universities. We worked with a purposefully selected group of MUPES and drew on theories of masculinities to thematically analyse the data from individual interviews and focus group discussions. The findings show that men are not always active producers of violence. While some intermittently reproduced hegemonic versions of masculinity that legitimate violence, most scrutinised and challenged the socio-cultural norms that valorise it. Not only did MUPES actively deconstruct some hegemonic masculine norms, but they also proposed a remaking of them and encouraged positive change in other men. We argue that male peer educators are valuable resources that may be engaged in university GBV intervention. [1] MUPES refers to male university undergraduate students recruited and trained by the Campus HIV/AIDS Support Unit (CHASU) for passing HIV/AIDS education to their university peers.